Guavira Fruit Pomace Promotes Immunomodulation and Reduction of Tumor Growth in Walker 256 Tumor-Bearing Rats - Zulin, Natália Eirão; Martins, Carolina G.; Appel, Márcia Helena; da Silva Coutinho, Débora Salles; Bialli, Amanda Plaça; Bronoski, Daiana Milena; Carvalhal, Stephanie R. S.; dos Santos, Elisvania Freitas; Loubet Filho, Paulo Sérgio; Bonatto, Sandro José Ribeiro; Fernandes, Luiz Cláudio; Cordeiro, Lucimara Mach Côrtes; et al. (Current Nutrition & Food Science, 2024)
Background: Guavira fruit is widely used for juice extraction purposes, and this process generates large amounts of pomace (waste). Guavira pomace was dried and milled to produce guavira pomace flour (GPF), which is rich in antioxidants and dietary fibers (polysaccharides). These compounds are known for their immunomodulatory and antitumor effects. Objective: To investigate whether GPF intake promotes immunomodulation and reduces Walker 256 tumor growth in rats. Methods: GPF was provided to Wistar rats in two different models: 1) 15-day Model, according to which, Walker 256 tumor-bearing rats received GPF (63 mg/200 g b.w./day) simultaneously to tumor growth for 15 days; 2) 45-day Model, according to which, tumor-bearing rats received GPF for 30 days before tumor cell implantation, as well as during tumor growth - it totaled 45 days. After animals were euthanized, tumors were collected and weighed, and tumor cells were isolated for proliferation capacity determination ex vivo. Enzymatic/colorimetric methods were used to determine resident peritoneal macrophages’ functionality, whereas blood T and B lymphocytes were assayed for proliferation capacity, ex vivo, under stimuli. Results: The 15-day Model did not show tumor mass or cell proliferation reduction in the treated group. GPF stimulated macrophage response in tumor-bearing and non-tumor-bearing rats. However, there was a substantial reduction in tumor mass and tumor cell proliferation under the 45-day Model. Macrophage and lymphocyte response decreased; it suggested that GPF can directly act in the tumor. Conclusion: Based on these findings, GPF has immunomodulatory and antitumor actions, and ingestion time plays a key role in them.
Keywords: guavira